Factors Affecting Nutritional Status (Height for Age) of Children Under Five in Rote Ndao District, Kupang, Nusa Tenggara Timur, Indonesia - Picauly, Intje; Boeky, Daniela; Oematan, Grouse (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Nusa Tenggara Timur (NTT) Province has many problems related to nutritional intake and public health. Pregnant women and children under five are groups of people who are very vulnerable to this problem. Many government programs have been implemented but to date there are still high maternal and infant mortality rates as well as high problems of malnutrition and stunting. This study aimed to determine what factors influence the nutritional status of toddlers in Rote Ndao Regency. Subjects and Method: This was a cross-sectional study conducted in Rote Ndao Regency, Kupang, NTT, Indonesia, from August to November 2023. A total of 43 mothers who had children aged 12-59 months were selected for this study. The dependent variable was nutritional status (height for age/ HAZ). The independent variables were maternal knowledge on nutrition and stunting, history of infectious diseases, and local-food-based supplementary feeding. Supplementary feeding was measured using food frequency questionnaire (FFQ). Nutritional status was measured by height for age. The data were analyzed using a multiple linear regression. Results: Maternal nutritional knowledge (b= 0.37; 95% CI = 0.23 to 0.50; p = 0.001), no history of infection (b= 0.98; 95% CI= 0.72 to 1.24; p= 0.001), and local-food-based supplementary feeding (b= 1.33; 95% CI= 0.71 to 1.96; p= 0.001) positively and significantly increased nutritional status (height for age) in children under five. Conclusion: Maternal nutritional knowledge, no history of infection, and local-food-based suplementary feeding positively and significantly increase nutritional status (height for age) in children under five.